Land Tenure, Farming Constraints, and Rural Livelihoods in India: An Integrated Assessment - V.Bansil Hans; Sajimon P.P (International Journal of Land, 2025)
Land remains the central asset shaping agricultural productivity, socio-economic security, and rural development in India. However, the complex interaction between land tenure systems, farming challenges, and livelihood patterns continues to hinder sustainable agricultural growth. This review provides an integrated assessment of the key issues influencing land use dynamics, including ownership inequalities, insecure tenancy arrangements, land fragmentation, and the slow implementation of land reforms. These structural limitations restrict farmers’ access to credit, technology, and institutional support, thereby reinforcing vulnerability among small and marginal cultivators. Alongside tenure-related constraints, Indian farmers face additional pressures from climate variability, declining soil health, groundwater depletion, and inadequate irrigation infrastructure. Traditional farming practices, limited mechanisation, and dependence on erratic monsoons further intensify risk exposure, affecting crop yields and income stability. Social factors such as migration, rural indebtedness, and the growing commodification of agricultural land also shape livelihood strategies, compelling many households to diversify their income sources beyond farming.
Keywords: Land Reform; Rural Development; agricultural productivity; and sustainable agriculture; land tenure